NEW DATA ON THE MICROBIOLOGY OF PULQUE - SANCHEZ MARROQUIN, AY (Instituto Politécnico Nacional, CD MEXICO, DF, MEX, 1950)
Necropsies of dogs in Mexico City demonstrate occurrence in many of them of S lupi, occurring in pea-sized to dove-egg-sized nodules in the walls of the esophagus and aorta The worms and the anatomical and histological anatomy of the nodules are descr
MEX AGRI
Keywords: NEW DATA, MICROBIOLOGY, PULQUE; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL; BOTANICA GENERAL